Treatment-Refractory Autoimmune Glial Fibrillary Acidic Protein Meningoencephalomyelitis in a Young Adult Female. (5th December 2022) - Arellano, Janetta; Sy, Michael
Abstract : Objective: To describe a case of autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy refractory to immunotherapy without evidence of malignancy or coexisting autoimmunity. Background: Autoimmune GFAP astrocytopathy is an autoimmune disease of the central nervous system associated with the presence of GFAP-IgG in the CSF. Patients may present with acute or subacute onset of headache, encephalopathy, seizures, abnormal vision, weakness or numbness, postural tremor and cerebellar ataxia. GFAP astrocytopathy is usually corticocorticosteroid-responsive in the acute setting but may rarely require maintenance immunotherapy to prevent relapse. Treatment refractory cases should trigger work up for coexisting autoimmunity or malignancy. Design/Methods: A 35-year-old female patient presented with subacute meningoencephalomyelitis with prodromal symptoms. Results: Her cerebrospinal fluid revealed lymphocytic pleocytosis and elevated protein. Brain magnetic resonance imaging (MRI) with and without contrast showed perivascular radial enhancement and periventricular T2 FLAIR hyperintensity. Spinal MRI with and without contrast demonstrated longitudinal T2 FLAIR hyperintensity from T1-T2 to T7-T8. Despite high dose steroid treatment, her disease progressed with an enlarging periventricular lesion and worsening visual acuity. Biopsy of the enhancing periventricular lesion showed perivascular inflammation. After five cycles of plasma exchange along with a five-day course of intravenous methylprednisolone 1 gram daily, her symptoms stabilized. The CSF autoimmune encephalopathy panel (Mayo Clinic Laboratories) came back positive for GFAP-IgG antibody on tissue immunofluorescence assay, and was confirmed positive by GFAP cell-based assay. No neoplastic disease was identified using high resolution PET/CT scans. Based on the aggressiveness of her disease, she received one cycle of cyclophosphamide, and was discharged home on an oral corticosteroid taper. Even one year after addition of both mycophenolate mofetil and rituximab, MRI imaging continued to reveal new enhancing lesions. Conclusions: Autoimmune GFAP astrocytopathy may sometimes require long-term immunosuppression even without presence of malignancy or other coexisting autoimmune disease.